Gender differences in the relationship between peer victimization and non-suicidal self-injury in adolescents with depressive disorders - Yin, Aihua; Liu, Shumiao; Wang, Chunyan; Wang, Yang; Qiao, Dongdong; Zhou, Yongjie (Frontiers in Psychology, 2025)
BackgroundNon-suicidal self-injury (NSSI) is common among adolescents with depressive disorders, yet the role of peer victimization and gender differences remains understudied. This study examines how different types of peer victimization (physical, verbal, social, property) relate to NSSI, focusing on gender as a moderator.MethodsA cross-sectional study of 2,343 adolescents with depressive disorders (517 males, 1,826 females) was conducted across 14 medical institutions in China. Peer victimization and NSSI were measured using the PVQ and C-FASM, respectively. Gender-stratified multiple linear regressions examined predictors of NSSI and its functions.ResultsNSSI was more prevalent in females (80.18%) than males (61.51%) (χ2 = 77.094, p < 0.001), with higher scores for emotion regulation (β = 12.33 vs. 9.85, p < 0.001). Regression analyses revealed gender-specific predictors: in males, social victimization (β = 1.213, p = 0.036) and verbal victimization (β = 1.764, p = 0.031) significantly predicted NSSI related to emotion regulation; in females, physical victimization (β = 0.768, p = 0.005) and social victimization (β = 0.873, p < 0.001) were the primary predictors. For attention-seeking functions, physical, social, and verbal victimization were significant predictors in both genders, with higher coefficients observed in males. It is noteworthy that property victimization was significantly associated with social avoidance-driven NSSI only in females (β = 0.564, p = 0.001), highlighting the gender-specific impact of victimization on NSSI functions.ConclusionPeer victimization is a significant predictor of NSSI, with clear gender-specific patterns. Gender-sensitive assessments and interventions tailored to victimization type are essential for early prevention.